The Influence of Social Media Usage and Physical Self-Concept on Social Anxiety Among Students of Universitas Persada Indonesia YAI - Muslimah Pradhanti, Aldila; Paramadina, Nisa (Lafadz Jaya Publisher, 2024)
This study explores the relationship between social media usage, physical self-concept, and social anxiety among students at Universitas Persada Indonesia YAI. Social media has become an essential aspect of daily life, especially among younger generations, significantly impacting various dimensions of their psychological well-being. Physical self-concept, which encompasses individuals' perceptions and evaluations of their physical attributes, also plays a crucial role in shaping self-esteem and social interactions. This research adopts a quantitative approach, utilizing convenience sampling to gather data from a sample of 200 students. The study employs three Likert scale-based instruments: the Social Anxiety Scale, Social Media Usage Scale, and Physical Self-Concept Scale. Data were analyzed using linear regression. The first hypothesis test revealed a t-value of 7.816, with a corresponding significance (Sig) value of 0.000, which is below the 0.05 threshold. This result supports the first hypothesis, indicating a positive and statistically significant relationship between social media usage and social anxiety. Similarly, the second hypothesis test yielded a t-value of -5.887, with a Sig value of 0.000, also below the 0.05 threshold. This finding confirms the second hypothesis, revealing a significant negative impact of physical self-concept on social anxiety. Overall, the study concludes that both social media usage and physical self-concept significantly influence social anxiety among Generation Z students at Universitas Persada Indonesia YAI.